2011
DOI: 10.1007/s00228-011-1160-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythropoiesis-stimulating agents in acute ST-segment elevation myocardial infarction: a systematic review

Abstract: Our meta-analysis indicates that the superiority of ESAs over conventional therapy in patients with acute STEMI is limited using current procedures. However, there is evidence to suggest that the timing and dosing of ESA administration may be optimized. Moreover, the long-term cardio-protective effect of ESAs in this patient population may be beneficial and worth exploring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…There was no significant benefit of ESAs on infarct size in a meta-analyses of patients with acute ST-segment elevation myocardial infarction [64, 65], and no effect on nonfatal heart related events in a meta-analysis of ESA-treated patients with heart failure [66]. There was also no difference in a meta-analysis of retinopathy of prematurity in infants treated with ESAs [67].…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant benefit of ESAs on infarct size in a meta-analyses of patients with acute ST-segment elevation myocardial infarction [64, 65], and no effect on nonfatal heart related events in a meta-analysis of ESA-treated patients with heart failure [66]. There was also no difference in a meta-analysis of retinopathy of prematurity in infants treated with ESAs [67].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, using both EPO and darbepoetin revealed that erythropoietin-stimulating agents with a higher first dose (>20,000 IU) or total dose (≥30,000 IU) improved LV ejection fraction more significantly when compared with that of lower doses (<20,000 IU). 21 High-dose EPO was superior to placebo, statistically improving LV ejection fraction by 1.02% and LV end systolic volume by −4.61 mL in patients with acute STEMI, and it was generally well tolerated. The adverse effects reported in patients receiving high-dose EPO were essentially consistent with those in the placebo group.…”
Section: Discussionmentioning
confidence: 87%
“…The dose of darbepoetin-α was chosen based on previous preclinical and clinical studies. [17][18][19] Thrombus aspiration or drug-eluting stent implantation was performed at the physician's discretion. TIMI flow grade and myocardial blush grade (MBG) were related with the prognosis of STEMI patients.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…However, a meta-analysis revealed that a higher dose of r-HuEPO (> 30,000 IU of epoetin-α) improved LVEF more significantly compared with the lower dose group (< 20,000 IU). 18) Accordingly, a high-dose of r-HuEPO may be more suitable for reducing reperfusion injury. Effect of intracoronary administration of erythropoietin in clinical studies: Intracoronary bolus administration of drugs results in higher concentration levels in the ischemic myocardium and local coronary bed.…”
Section: Efficacy Of Intracoronary Darbepoetin-α In Stemimentioning
confidence: 99%